KONSEPSI KETUHANAN DALAM GEGURITAN JAPATUAN (TELAAH SINGKAT PERSPEKTIF FILOSOFIS) - I Made Suweta (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Geguritan Japatuan in the story there are two main characters who have different characters in observing something. Based on this background, there are three formulations to be discussed, namely: (1) what is the teaching structure contained in Geguritan Japatuan?, (2) what is the concept of divinity in the Geguritan Japatuan text?, and (3) how is local wisdom contained in Geguritan Japatuan text? In data discovery used literature study techniques, while in data analysis used descriptive qualitative techniques; while in writing, verbal language is used narratively, with a combination of inductive and deductive techniques. Structurally, the Geguritan Japatuan text can be divided into three parts: introduction, content, and closing. The concept of God in Geguritan Japatuan is the mention of the name of God as a manifestation of God, namely: Lord Shiva, Lord Vishnu, and Lord Indra; While Local Wisdom in Geguritan Japatuan is related to Catur Sanak.